2012
DOI: 10.1152/ajpheart.00716.2011
|View full text |Cite
|
Sign up to set email alerts
|

Nestin+cells and healing the infarcted heart

Abstract: Calderone A. Nestin ϩ cells and healing the infarcted heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 66 publications
2
23
0
4
Order By: Relevance
“…Interestingly, the aforementioned findings and spatiotemporal patterns of nestin-positive cells are analogous to those described for cells derived from the adventitial fibroblasts following brain infarct (Brierley and Brown 1982). In addition, nestin is induced in fibroblast-like cells under fibrotic conditions or after injury in various tissues including heart and kidney (Calderone 2012;Kishaba et al 2010). Our data raise the possibility that these nestin-positive cells are derived from fibroblasts comprising the vascular adventitia of the larger caliber vessels at this later time point, when the capillary bed is actually being destroyed.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Interestingly, the aforementioned findings and spatiotemporal patterns of nestin-positive cells are analogous to those described for cells derived from the adventitial fibroblasts following brain infarct (Brierley and Brown 1982). In addition, nestin is induced in fibroblast-like cells under fibrotic conditions or after injury in various tissues including heart and kidney (Calderone 2012;Kishaba et al 2010). Our data raise the possibility that these nestin-positive cells are derived from fibroblasts comprising the vascular adventitia of the larger caliber vessels at this later time point, when the capillary bed is actually being destroyed.…”
Section: Discussionsupporting
confidence: 62%
“…Nevertheless, increasing evidence has identified nestin as an intermediate filament protein that interacts with other cytoskeleton proteins. Nestin is involved in cell division, the structural integrity and mobility of cells and tissue stability (Calderone 2012;Chen et al 2006;Herrmann and Aebi 2000;Wang and Stamenovic 2000). Nestin is also reactivated in response to injury during tissue and wound healing (for a review, see Wiese et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These PCs likely originate from SGCs [10]. In human and rat trigeminal ganglia SGCs were found positive for nestin, a marker of neuroepithelial stem cells [13][14][15][16][17]. Nestin expression in cells may indicate multi-potentiality and regenerative potential [18].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] Importantly, previous studies have reported that Nestin was up-regulated in the infarcted myocardium within 48 hours, and further indicated that Nestin + cells participate in the wound healing NESTIN + CELLS ENHANCE SURVIVAL OF DOXORUBICIN INDUCED HL-1 CELLS after myocardial injury. 20,21) However, whether Nestin + cells participated in the pathogenesis of the DCM has not been reported yet.…”
mentioning
confidence: 99%